Adiponectin concentrations among patients with diabetes in a multi ethnic population of Malaysia - Mohamed, Hamid Jan Jan (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2011)
Objectives: To determine whether adiponectin concentrations differ between Malays, Chinese and Indians with type 2 diabetes and to investigate if adiponectin is associated with dietary intake and physical activity in these ethnics. Methods: A total of 210 newly diagnosed type 2 diabetes patients (Malays, Chinese and Indians) were recruited from Sg Bakap Hospital in Penang, Malaysia. Data on demographic background, clinical, anthropometric, dietary intake, and physical activity were obtained. Serum adiponectin and standard laboratory test were performed according to standard procedure. Objectives: To determine whether adiponectin concentrations differ between Malays, Chinese and Indians with type 2 diabetes and to investigate if adiponectin is associated with dietary intake and physical activity in these ethnics. Methods: A total of 210 newly diagnosed type 2 diabetes patients (Malays, Chinese and Indians) were recruited from Sg Bakap Hospital in Penang, Malaysia. Data on demographic background, clinical, anthropometric, dietary intake, and physical activity were obtained. Serum adiponectin and standard laboratory test were performed according to standard procedure.